Altered serum interleukin-7 and interleukin-10 are associated with drug-free major depressive disorder - Sadia Anjum; M. M. A. Shalahuddin Qusar; Mohammad Shahriar; Sardar Mohammad Ashraful Islam; Mohiuddin Ahmed Bhuiyan; Md. Rabiul Islam (SAGE Publishing, 2020)
Background: Abnormal expression of inflammatory cytokines in major depressive disorder (MDD) suggests the activation of an inflammatory process. The pattern of alterations in cytokine levels is still ambiguous. The present study aimed to evaluate interleukin-7 (IL-7) and interleukin-10 (IL-10) for their involvement in the pathophysiology of MDD and determine their relationships with depression risk. Methods: The study included 166 medication-free subjects: 84 MDD patients and 82 sex- and age-matched healthy controls (HCs). A qualified psychiatrist diagnosed patients and evaluated controls based on the Diagnostic and Statistical Manual of Mental Disorders , 5th edition (DSM-5). Hamilton depression rating scale (Ham-D) was used to measure the severity of depression in MDD patients. Serum IL-7 and IL-10 levels were measured using enzyme-linked immunosorbent assay (ELISA) kits. Results: Compared with HCs, the serum levels of IL-7 were significantly decreased, whereas that of IL-10 increased in MDD patients. Moreover, the severity of depression is correlated with the altered levels of IL-7 and IL-10 in MDD patients. We found a negative correlation between IL-7 and Hamilton depression rating (Ham-D) scores ( r  = -0.580, p  < 0.05), whereas there was a positive correlation between IL-10 and Ham-D scores ( r  = 0.555, p  < 0.05). Conclusions: The altered levels of serum IL-7 and IL-10 in MDD patients may represent a homeostatic mechanism that enhances the inflammatory process during depression. The alterations of these cytokine levels in MDD and their association with the severity of depression support them as promising, but there may still be controversial factors for understanding the pathophysiology of depression.